Penilaian Kinerja Karyawan Dengan Mengunakan Metode Balanced Srocecard Pada PT Dolphin Food & Beverage Tangerang - Rafi Adi Saputra; Dedy Syahyuni; Lady Diana Warpindyastuti (STIKes Ibnu Sina Ajibarang, 2024)
Human resources owned by a company are an important key to the running of a company which includes the role of managing and utilizing employees to spur employee morale. The purpose of this study was to assess employee performance using the balanced scorecard method at PT Dolphin Food & Beverage Tangerang. This research uses non-statistical quantitative methods with a sample of 3 employees with data collection in the form of interviews. Data analysis techniques using a comparative approach that is by comparing between performance appraisal conducted by PT Dolphin Food & Beverage Tangerang with performance appraisal based on Balanced Scorecard expressed descriptively. The results of this study indicate that the use of the Balanced Scorecard (BSC) method has a positive impact on employee performance appraisal at PT Dolphin Food & Beverage Tangerang through the perspective of the balanced scorecard. Compared to the Management by Objectives (MBO) method, the application of Balanced Scorecard at PT Dolphin Food & Beverage Tangerang shows many advantages. BSC provides a broader approach by taking into account its four main perspectives, resulting in a clearer picture of employee performance.